Antibacterial Nanoparticles with Natural Photosensitizers Extracted from Spinach Leaves - Ludačka, Pavel; Kubát, Pavel; Bosáková, Zuzana; Mosinger, Jiří (ACS omega, 2022)
We prepared antibacterial polystyrene nanoparticles (NPs) with natural photosensitizers from chlorophyll (Chl) extract via a simple nanoprecipitation method using the same solvent for dissolution of the polystyrene matrix and extraction of Chls from spinach leaves. A high photo-oxidation and antibacterial effect was demonstrated on Escherichia coli and was based on the photogeneration of singlet oxygen O2(1Δg), which was directly monitored by NIR luminescence measurements and indirectly verified using a chemical trap. The photoactivity of NPs was triggered by visible light, with enhanced red absorption by Chls. To reduce the quenching effect of carotenoids (β-carotene, lutein, etc.) in the Chl extract, diluted and/or preirradiated samples, in which the photo-oxidized carotenoids lose their quenching effect, were used for preparation of the NPs. For enhanced photo-oxidation and antibacterial effects, a sulfonated polystyrene matrix was used for preparation of a stable dispersion of sulfonated NPs, with the quenching effect of carotenoids being suppressed.